Studi Literatur: Model Pembelajaran Problem-Based Learning Terhadap Perkembangan Kognitif Anak Usia Sekolah Dasar: Literature Review: The Effect of Problem-Based Learning on the Cognitive Development of Elementary School-Aged Children - Ayu Uswah Munjiah; Rena Komalasari; Millah Fithriyani (Paidagogia: Jurnal Pengajaran dan Pendidikan, 2024)
The Problem-Based Learning (PBL) model is an approach aimed at enhancing critical thinking and problem-solving skills in elementary school-aged children. At this developmental stage, students are capable of more logical and concrete thinking, and they begin to understand cause-and-effect concepts and connect ideas more effectively. In addition to their growing memory capabilities, students at this stage also start to learn how to plan and make decisions based on rational thinking. Therefore, the implementation of Problem-Based Learning (PBL) emphasizes active involvement of students in the learning process through the resolution of real-life problems that are relevant to their everyday lives.This research aims to analyze the influence of PBL on the cognitive development of elementary school students through a literature review method. Based on the literature study, PBL has been shown to be effective in stimulating cognitive development in students, particularly in critical, logical, and analytical thinking aspects. Through this approach, students are not only required to understand concepts but also to apply their knowledge in real-world situations. This research provides in-depth insights into the importance of PBL in enhancing the cognitive development of elementary school students.